SIDE EFFECTS MONITORING OF TEMULAWAK RHIZOME, GINGER, SOYBEAN AND SHRIMP SHELL EXTRACTS IN COMBINATION COMPARED TO DICLOFENAC SODIUM IN OSTEOARTHRITIS PATIENTS - Haslinda Haslinda; Nyoman Kertia; Arif Nurrochmad (Faculty of Pharmacy, Universitas Gadjah Mada)
Non-steroidal anti-inflammatory drugs such as diclofenac sodium were common drug given worldwide to reduce pain in osteoarthritis. The long-term used of diclofenac sodium side effects was on liver, kidney, gastrointestinal and other organs. The earlier study result have shown the effectiveness of the combination of temulawak rhizome extract, ginger, soy and shrimp shells in osteoarthritis patients. This third phase of clinical study purpose was to monitor the side effects of temulawak rhizome, ginger, soybean and shrimp shells extract in combination compared to diclofenac sodium in patients with osteoarthritis. Forty seven patients with knee osteoarthritis diagnosed by American College of rheumatology criteria were included in this study. This subject were devided randomly into two groups to receive either the combination of temulawak rhizome 100 mg, ginger 100 mg, soy 50 mg and shrimp shells 50 mg extract (n=23) or diclofenac sodium 25 mg (n = 24) three times a day orally for 14 days. The side effect that were monitored were side effect that appear in the gastrointestinal organs, cardiovascular, central nervous system and other organs for 14 days therapy and laboratory tests of SGOT, SGPT, creatinin serum, urea, hemoglobin, leukocytes and platelets were performed before and after 14 days. Chi-Square test were used to evaluate the side effects and independent t test or Mann-Whitney tests were used to evaluate changes of levels of SGOT, SGPT, serum creatinine, serum urea, hemoglobin, leukocytes and platelets before and after intervention. Percentage of side effects on the gastrointestinal organs, cardiovascular, central nervous system and other organs in combination of ginger rhizome 100 mg, 100 mg of ginger, 50 mg of soy and 50 mg of shrimp shell extract group was not significantly different compared to diclofenac sodium 25 mg. SGPT activity in trial group was decrease significantly (p <0.05) compared to diclofenac sodium 25 mg but no significant difference in liver function (SGOT), kidney function (creatinine and urea), and bone marrow function (hemoglobin, leukocytes, and platelets).Keywords: Osteoarthritis, combination of temulawak rhizome, ginger, soy and shrimp shells, diclofenac sodium, side effects, liver function, kidney function and bone marrow.